Analysis of the 1.1-Mb Human α/δ T-Cell Receptor Locus with Bacterial Artificial Chromosome Clones - Boysen, Cecilie; Simon, Melvin I.; Hood, Leroy (Genome Research, 1997)
Bacterial artificial chromosome (BAC) clones are effective mapping and sequencing reagents. The 1.1-Mb α/δ T-cell receptor locus of humans was mapped and partially sequenced with BAC clones. Seventeen BAC clones covered the 1.1-Mb α/δ locus, with the exception of one small gap that was expected from the coverage that a 3.7-fold BAC library is likely to provide. The end sequences of the BAC inserts could be obtained directly from the BAC DNA by sequencing with the chain terminator chemistry. Five complete BAC inserts were sequenced directly by the shotgun approach. The ends of the 17 BAC inserts were distributed evenly across the locus. By several independent criteria, the BAC clones faithfully represented the genomic DNA, with the exception of a single clone with a 68-kb deletion. These BAC features led to the proposal of a new approach to sequence the human genome.[The sequenced BAC clones, BAC956, BAC810, BAC480, BAC378, and BAC129, have been submitted to GenBank under accession nos.U85199, U85198, U85197, U85196, and U85195, respectively.]
10.1101/gr.7.4.330